Pengaruh Pendekatan STEM Berbantuan Flipbook Digital terhadap Kemampuan Literasi Sains Siswa Sekolah Dasar - Rahmah, Deliyan Nadifa; Rahayu, Puji; Suwangsih, Erna (AS-SABIQUN, 2023)
This research was motivated2by the low science literacy1ability of grade 4 elementary5school students. This study aims to find out: 1) the improvement of science literacy skills0of students4who use digital flipbook-assisted STEM approaches is better than students who use scientific approaches; 2) the effect of digital flipbook-assisted STEM approaches on students' science literacy skills. This1type1of research is quasi-experimental. The sample6of this study1was grade 4 elementary school students, consisting of grade 4 A7as an experimental2class and grade 4 B as8a control9class. The instruments in this study are in the form of science literacy ability tests and5non-tests in the form of student worksheets6and documentation. The results of data analysis showed that the experimental class using the digital flipbook-assisted1STEM approach obtained an0increase of 0.81 (high1category) while1the control class using a scientific approach7obtainedyan increase of 0.42 (medium0category) and there was an influence2ofcthe digital flipbook-assisted1STEM approach in increasing students' science literacy0skills by 28.9%. The conclusions of this study are: (1) Learning with a digital flipbook-assisted STEM approach is better at improving students' science4literacy skills5compared to scientific approaches; (2) The digital flipbook-assisted STEM2approach has an influence on5the science7literacy skills of elementary school0students.